1992
DOI: 10.1111/j.1365-2796.1992.tb00976.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity due to repeated intake of low doses of paracetamol

Abstract: The cases of two patients with fulminant hepatic failure after intake of therapeutic doses (4-8 g) of paracetamol, and who were admitted to hospital for assessment for liver transplantation, are described. In both patients starvation, due to abdominal pain, nausea and vomiting or diarrhoea, was probably contributing to the toxic effect of the drug. One of the patients also had an excessive alcohol intake. Paracetamol should not be prescribed for patients with alcoholism or with low food intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 15 publications
1
52
0
1
Order By: Relevance
“…Paracetamol is a common antipyretic agent, which is safe in therapeutic doses but can produce fatal hepatic necrosis in man, rats and mice with toxic doses [23][24][25] . Protection against paracetamol-induced toxicity has been used as a test for potential hepatoprotective activity by several investigations [26][27][28][29][30] .…”
Section: Resultsmentioning
confidence: 99%
“…Paracetamol is a common antipyretic agent, which is safe in therapeutic doses but can produce fatal hepatic necrosis in man, rats and mice with toxic doses [23][24][25] . Protection against paracetamol-induced toxicity has been used as a test for potential hepatoprotective activity by several investigations [26][27][28][29][30] .…”
Section: Resultsmentioning
confidence: 99%
“…The development of this assay provides a tool for the systematic study of APAP toxicity in humans following toxic exposures or therapeutic misadventures with APAP. Recent literature has highlighted the occurrence of therapeutic misadventures with APAP (Seeff et al, 1986;Eriksson et al, 1992;Bonkovsky et al, 1994;Whitcomb and Block, 1994;Rivera-Penera et al, 1997;Heubi et al, 1998). These articles describe the development of hepatotoxicity in patients using APAP with therapeutic intent.…”
Section: Discussionmentioning
confidence: 99%
“…These are generally categorized as either conditions that increase the production of the reactive metabolite NAPQI or that decrease the ability to detoxify NAPQI (e.g., decreased concentration of glutathione). Authors report that low daily doses of acetaminophen, ranging from minimal daily doses of 2.4-6 g in alcoholics, patients with starvation, or those on chronic antituberculous medications have been associated with elevated aminotransferase levels (40,(64)(65)(66). Case reports (level 4), case series (level 4), and cohort (level 2b) or case-control (level 3b) studies have reported either greater severity of injury or a lower threshold dose for the development of hepatotoxicity after acetaminophen ingestion by patients chronically ingesting alcohol or other compounds thought to increase susceptibility to acetaminophen toxicity (e.g., isoniazid use, prolonged fasting) (2,34,(36)(37)(38)40,41,46,50,65,(67)(68)(69)(70)(71)(72).…”
Section: Repeated Supratherapeutic Ingestion (Rsti) By Patients 6 Yeamentioning
confidence: 99%